2015
DOI: 10.1002/2014je004719
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for explosive silicic volcanism on the Moon from the extended distribution of thorium near the Compton‐Belkovich Volcanic Complex

Abstract: the Moon, using data from the Lunar Prospector Gamma Ray Spectrometer. We enhance the resolution via a pixon image reconstruction technique and find that the thorium is distributed over a larger (40 km × 75 km) area than the (25 km × 35 km) high-albedo region normally associated with Compton-Belkovich. Our reconstructions show that inside this region, the thorium concentration is 14-26 ppm. We also find additional thorium, spread up to 300 km eastward of the complex at ∼ 2 ppm. The thorium must have been depos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…These explosively deposited materials can still be exposed within the highlands westward of the domes but would be buried by the mare and highland plains elsewhere. The similar mechanism of explosive pulverization of volcanic materials was recently proposed ( Wilson et al, 2015 ) to explain formation of an extensive thorium anomaly around the volcanic complex in the Compton-Belkovich region ( Joliff et al, 2011 ).…”
Section: Discussion: Characteristics and Potential Modes Of Emplacementmentioning
confidence: 55%
“…These explosively deposited materials can still be exposed within the highlands westward of the domes but would be buried by the mare and highland plains elsewhere. The similar mechanism of explosive pulverization of volcanic materials was recently proposed ( Wilson et al, 2015 ) to explain formation of an extensive thorium anomaly around the volcanic complex in the Compton-Belkovich region ( Joliff et al, 2011 ).…”
Section: Discussion: Characteristics and Potential Modes Of Emplacementmentioning
confidence: 55%
“…Magmas enriched in incompatible elements (e.g., Th) typically require multiple processing episodes to form, but the observed distribution and compositional range of lunar silicic materials are difficult to explain with current models of lunar magma fractionation (e.g., Hawke et al, 20 03;Hagerty et al, 20 06;Jolliff et al, 2011Jolliff et al, , 2012Kusuma et al, 2012 ). Nevertheless, both telescopic and orbital observations of morphologically and compositionally distinct constructs, including the nearside lunar red spots (regions of strong ultraviolet (UV) absorption), have supported non-mare, Si-rich volcanic interpretations (e.g., Whitaker, 1972a;Malin, 1974;Wood and Head, 1975;Head and McCord, 1978;Müller et al, 1986;Chevrel et al, 1999;Hawke et al, 2001Hawke et al, , 2003Hagerty et al, 2006;Glotch et al, 2010;Wagner et al, 2010;Glotch et al, 2011;Jolliff et al, 2011;Kusuma et al, 2012;Lawrence et al, 2014;Wilson et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pixon method (Pina & Puetter, ) has successfully been used in a range of disciplines including medical imaging and infrared and X‐ray astronomy (Puetter, , and references therein). In addition, it has recently been used to reconstruct remotely sensed neutron (Eke et al, ; Wilson et al, ) and gamma ray data (Lawrence et al, ; Wilson et al, ) and has been shown to give a spatial resolution 1.5–2 times that of other methods in reconstructing planetary data sets (Lawrence et al, ). A modified pixon technique in which the reconstructed image is the result of combining decoupled regions has been developed for use when sharp boundaries are expected to exist based on other data (Eke et al, ; Wilson et al, ).…”
Section: Image Reconstruction In Planetary Sciencesmentioning
confidence: 99%